Impact of tablet PCs on learning outcomes in a classroom environment. (1st July 2019) - Javed, Yasir; Samara, Khalid
It is evident that information and communication technology (ICT) plays a vital role in educational settings. However, it is also important to determine how learners use ICT in different settings. Currently, ICT is mostly used as a supporting tool for the existing learning process, however, it is still unable to revolutionise the learning and teaching process. The reason for this can be its failure to unleash its original potential and capabilities. This study adopted a quasi-experimental method to measure the impact of using tablet PCs on the learning outcomes of 255 children inside classrooms. Data was collected from both types of classroom, i.e., classrooms using and not using mobile tablets for learning and the difference-in-differences technique has been coupled with a t-test to make the comparison. The results show that children using tablet-PCs in the classroom have better learning outcomes.